2005
DOI: 10.1038/sj.cdd.4401759
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid induces extracellular signal-regulated kinase 1/2 activation and inhibits apoptosis in endothelial cells

Abstract: The histone deacetylase (HDAC) inhibitor valproic acid (VPA) was recently shown to inhibit angiogenesis, but displays no toxicity in endothelial cells. Here, we demonstrate that VPA increases extracellular signal-regulated kinase 1/2 (ERK 1/2) phosphorylation in human umbilical vein endothelial cells (HUVEC). The investigation of structurally modified VPA derivatives revealed that the induction of ERK 1/2 phosphorylation is not correlated to HDAC inhibition. PD98059, a pharmacological inhibitor of the mitogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 35 publications
9
77
2
Order By: Relevance
“…Importantly, our report is the first to demonstrate that HDACs can modulate a number of intracellular signalling cascades in response to growth factors. This appeared to be a TGF-β-specific effect, because in the absence of the growth factor HDAC inhibitors activated MAPK signalling, as previously noted for VPA (Michaelis et al, 2006). Furthermore, when examining IL-1 activation of MAPK we found no repression by TSA, albeit in cultured human articular chondrocytes (Supp.…”
Section: Discussionmentioning
confidence: 68%
“…Importantly, our report is the first to demonstrate that HDACs can modulate a number of intracellular signalling cascades in response to growth factors. This appeared to be a TGF-β-specific effect, because in the absence of the growth factor HDAC inhibitors activated MAPK signalling, as previously noted for VPA (Michaelis et al, 2006). Furthermore, when examining IL-1 activation of MAPK we found no repression by TSA, albeit in cultured human articular chondrocytes (Supp.…”
Section: Discussionmentioning
confidence: 68%
“…Pettersson et al (31) also suggested that the activation of ERK was essential for the retinoid-induced apoptosis of breast cancer cells. Michaelis et al (13) reported that valproic acid increases the level of ERK 1/2 phosphorylation in human umbilical vein endothelial cells. These results provide evidence for a novel signaling pathway that mediates apicidininduced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Apicidin is a novel cyclic tetrapeptide with potent broadspectrum anti-protozoal activity against apicomplexan parasites and anti-proliferative activity against various cancer cell lines (13,14). However, the precise mechanism of how apicidin regulates apoptosis in ras-activated human breast epithelial cells is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Cell cycle was determined using a commercial kit (BD Biosciences, San Jose, CA) according to the manufacturer's instructions as described previously [33].…”
Section: Cell Cycle Analysismentioning
confidence: 99%